External Validation of BMT-i Computerized Test Battery for Diagnosis of Learning Disabilities - Billard, Catherine; Jung, Camille; Munnich, Arnold; Gassama, Sahawanatou; Touzin, Monique; Mirassou, Anne; Willig, Thiébaut-Noël (Frontiers in Pediatrics, 2021)
Background: Learning disabilities (LDs) are a major public health issue, affecting cognitive functions and academic performance for 8% of children. If LDs are not detected early and addressed through appropriate interventions, they have a heavy impact on these children in the social, educational, and professional spheres, at great cost to society. The BMT-i (Batterie Modulable de Tests informatisée, or “computerized Adaptable Test Battery”) enables fast, easy, reliable assessments for each cognitive domain. It has previously been validated in children ages 4–13 who had no prior complaints. The present study demonstrates the sensitivity of the BMT-i, relative to reference test batteries, for 191 children with cognitive difficulties. Materials and Methods: These 191 subjects were included in the study by the 14 pediatricians treating them for complaints in five cognitive domains: written language [60 (cases)]; mathematical cognition (40); oral language (60); handwriting, drawing, and visuospatial construction (45); and attention and executive functioning (45). In accordance with a predefined protocol, the children were administered BMT-i tests first, by their pediatricians, and reference tests later, by specialists to whom the BMT-i test results were not disclosed. Comparison of BMT-i and reference test results made it possible to evaluate sensitivity and agreement between tests. Results: For each of the five domains, the BMT-i was very sensitive (0.91–1), and normal BMT-i results were highly predictive of normal results for specialized reference tests [negative likelihood ratio (LR–): 0–0.16]. There was close agreement between BMT-i and reference tests in all domains except attention and executive functioning, for which only moderate agreement was observed. Conclusion: The BMT-i offers rapid, reliable, simple computerized assessments whose sensitivity and agreement with reference test batteries make it a suitable first-line instrument for LD screening in children 4–13 years old.